Comparison of anatomical thermal ablation and routine thermal ablation for hepatocellular carcinoma≤50 mm: A propensity score matching. Issue 7 (25th May 2022) - Li, Kai; Long, Yinglin; He, Xuqi; Wu, Yuxuan; Xu, Jianliang; Ye, Huolin; Xu, Erjiao; Zeng, Qingjing; Chen, Jianning; Yuan, Lianxiong; Zheng, Rongqin
Abstract: Aim: The present study was to evaluated the clinical value of anatomical thermal ablation to treat hepatocellular carcinoma compared with routine thermal ablation. Methods: Hepatocellular carcinoma patients with tumor diameter ≤50 mm treated by thermal ablation at our center were retrospectively enrolled from October 2015 to December 2018. Enrolled patients were grouped into the anatomical ablation group and routine ablation group, respectively. To minimize the effects of potential confounders from selection bias, a propensity score matching was carried out. Technical efficacy, recurrence and survivals rates were compared. Results: Altogether 101 patients (119 lesions) were grouped into the anatomical ablation group and 101 patients (131 lesions) into the routine ablation group. The ablation zone volume of the anatomical ablation group was 36.8 (2.5–176.9) ml, significantly larger than that of the routine ablation group (28.5 [28.5 (2.8–184.3) ml] ( p  = 0.005)). Adjusted with propensity score matching, The 1‐, 2‐, and 3‐year local recurrence rates were 0.0%, 0.0%, and 0.0% for the anatomical ablation group and 6.9%, 10.1%, and 10.1% for the routine ablation group, respectively ( p  = 0.013). The cumulative 1‐, 2‐, and 3‐year progression‐free survival rates were 93.4%, 82.7%, and 79.0% for the anatomical ablation group, 74.2%, 56.9%, and 51.6% for the routine ablation group ( p  = 0.001). Conclusions: Anatomical ablation could be a favorable ablation strategy to improve therapeutic effect of thermal ablation for HCC with visible feeding vessels and reserved liver function.